Normative data for interpreting the SNOT‑22: rhinology = Valori di riferimento per interpretare lo SNOT-22 - Plath, Michaela; Sand, Matthias; Cavaliere, Carlo; Plinkert, Peter K.; Baumann, Ingo; Plath, Karim (Acta otorhinolaryngologica italica, 2023)
Objectives. The Sino-Nasal Outcome Test 22 (SNOT‑22) is a validated patient-reported outcome instrument to evaluate the health-related quality of life (HRQoL) in patients with chronic rhinosinusitis (CRS). There are no published normative SNOT‑22 scores, limiting its interpretation. Methods. Symptom scores from 1,000 SNOT‑22 questionnaires were analysed by principal component analysis (PCA) and exploratory factor analyses. Data were derived from a survey with 1,000 healthy Europeans (reference cohort) who were recruited using the Respondi panel for market and social science research. This subsample was quoted to the population distribution of the German Microcensus and selected from a non-probability panel.Results. The overall normative SNOT‑22 score can be detected to be 20.2 ± 19.44. Male (18.49 ± 19.15) and older (> 50 years old; 18.3 ± 17.49) participants had overall lower SNOT‑22 mean results than females (21.8 ± 19.6) and younger (21.4 ± 20.55) participants, indicating higher levels of satisfaction. PCA proposed two SNOT‑22 domains (“physiological well-being” and “psychological well-being”), which explained 65% of the variance. Conclusions. These are the first published (German) normative scores for the SNOT‑22 and provide a clinical reference point for the interpretation of data.
Gesehen am 08.10.2024